Zika virus: raising awareness to prevent a pandemic - Alam, Mohammad Khursheed; Arshad, Anas Imran (Bangladesh Journal of Medical Science, 2018)
Zika virus is a flavivirus which is transmitted through Aedes female mosquito species or sexually. “Mild dengue” like symptoms are noticed which usually subside shortly and uneventfully. In 1969 ZIKV was isolated in West Malaysia for the first time. Since then no case has been reported in Malaysia. WHO has declared a global threat of an epidemic spread after the outbreak in Brazil. Rain forest climate regions are at a constant state of emergency as pools of water are abundantly formed as a result of rain showers throughout the year which provides a habitat for mosquitos. We try to raise awareness and alert health governing bodies and institutions to take necessary steps to prevent and eradicate the potential pandemic threat. Counselling of females who are planning to conceive is required to minimize the threat to newborn babies. Travellers visiting the equatorial regions should be screened and counselled to detect and prevent viral infection transfer and to avoid complications on a larger scale. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.327-328